A critical review of the ship investment literature - Andreou, Panayiotis; Karasamani, Isabella (My University, 2019)
This chapter identifies studies of the main pillars of ship investment research and integrate theoretical thinking. In conducting a critical review, it is important to identify, assess, and systematically review all relevant studies using a transparent process that will safeguard replicability. Primary and secondary dynamics of yield premia are of key importance for the investment community, since information on changes in yield premia can be used for investment and asset allocation purposes, and for shipping firms who need bond financing to keep up with intensified capital requirements. The chapter discusses the use of panel methodology in investigating the determinants of credit spread changes in the bond financing frame. It reviews the ship investment literature for the three topics of interest, namely, when and how to invest, how to manage the investment, and how to raise the funds for the investment. The chapter provides the structure of the extant studies, their nature, and the provision of implications and recommendations for research.